Pulmonary Ablation: A Primer. Issue 2 (May 2014) - Roberton, Benjamin J.; Liu, David; Power, Mark; Wan, John M.C.; Stuart, Sam; Klass, Darren; Yee, John
Percutaneous image-guided thermal ablation is safe and efficacious in achieving local control and improving outcome in the treatment of both early stage non–small-cell lung cancer and pulmonary metastatic disease, in which surgical treatment is precluded by comorbidity, poor cardiorespiratory reserve, or unfavorable disease distribution. Radiofrequency ablation is the most established technology, but new thermal ablation technologies such as microwave ablation and cryoablation may offer some advantages. The use of advanced techniques, such as induced pneumothorax and the popsicle stick technique, or combining thermal ablation with radiotherapy, widens the treatment options available to the multidisciplinary team. The intent of this article is to provide the reader with a practical knowledge base of pulmonary ablation by concentrating on indications, techniques, and follow-up.